2019
DOI: 10.1002/jcp.28592
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key genes and pathways in benign prostatic hyperplasia

Abstract: Benign prostatic hyperplasia (BPH) is one of the most common causes of lower urinary tract symptoms (LUTS) in elderly man. However, the underlying molecular mechanisms of BPH have not been completely elucidated. We identified the key genes and pathways by using analysis of Gene Expression Omnibus (GEO) database.Differentially expressed genes (DEGs) were identified using edgeR. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses were performed for the DEGs by Database for Annotation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…Qiu et al [31] demonstrated the regulation role of tumor-associated macrophages in BCa cell growth. Xue et al [32] also indicated that the infiltration of M2 macrophage might be an underlying target of immunotherapy for BCa patients. Previous studies have demonstrated that tumor-infiltrating T cell landscape in bladder cancer would contribute to management decisions making, particularly immunotherapy [33].…”
Section: Discussionmentioning
confidence: 99%
“…Qiu et al [31] demonstrated the regulation role of tumor-associated macrophages in BCa cell growth. Xue et al [32] also indicated that the infiltration of M2 macrophage might be an underlying target of immunotherapy for BCa patients. Previous studies have demonstrated that tumor-infiltrating T cell landscape in bladder cancer would contribute to management decisions making, particularly immunotherapy [33].…”
Section: Discussionmentioning
confidence: 99%
“…The DAVID online tool (https://david.ncifcrf.gov/) was used to annotate the survival‐related mRNAs as previously described (Ke et al, ; Xu et al, ; Xu, Wu, Yin, Xue, & Gou, ). REACTOME (http://www.reactome.org/), Kyoto Encyclopedia of Genes and Genomes (KEGG) (http://www.genome.jp/kegg/pathway.html), and BIOCARTA (https://cgap.nci.nih.gov/Pathways/BioCarta_Pathways) pathway databases were used to perform pathway analyses among survival‐related mRNAs screened by univariate Cox analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The Cytoscape version 3.7.2 was used to constructed networks, which is a java based open source software (Demchak et al, 2014). Functional pathways of resveratrol related to NDs were analyzed using GO enrichment and KEGG pathways analysis based upon the database for Annotation, Visualization and Integrated Discovery (DAVID) version 6.8 (https://david.ncifcrf.gov/) (Ke et al, 2019). P < 0.05 suggested the enrichment degree had statistically significant and the pathway results might be essential functional mechanisms of resveratrol in the treatment of NDs.…”
Section: Go Function Enrichment and Kegg Pathway Analysismentioning
confidence: 99%